2007
DOI: 10.1042/bj20070384
|View full text |Cite
|
Sign up to set email alerts
|

A novel murine protein with no effect on iron homoeostasis is homologous with transferrin and is the putative inhibitor of carbonic anhydrase

Abstract: In a search for genes that modify iron homoeostasis, a gene (1300017J02Rik) was located immediately upstream of the murine TF (transferrin) gene. However, expression of the 1300017J02Rik gene product was not responsive to a number of modulators of iron metabolism. Specifically, expression was not altered in mouse models of iron disorders including mice with deficiencies in the haemochromatosis protein Hfe, the recombination-activating protein, Rag, beta2-microglobulin, TF, ceruloplasmin or Hb, or in mice with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 52 publications
(70 reference statements)
1
27
0
Order By: Relevance
“…Additionally, and as reported previously (44), the single rate constant is very slow (0.46 min -1 at 295 and 0.60 min -1 at 280) requiring 500 sec to attain 5 half lives. This result contrasts with iron release from the monoferric N-lobe (Fe N hTF) that yielded three rate constants of 20.8, 4.1 and 1.1 min -1 under identical conditions and was complete in 200 sec (25). The slower rate constant for iron release from the C-lobe of Fe C hTF relative to the N-lobe in the Fe N hTF construct is attributed to differences in the second shell residues and in the hinge regions between the subdomains of each lobe.…”
Section: Discussionmentioning
confidence: 74%
“…Additionally, and as reported previously (44), the single rate constant is very slow (0.46 min -1 at 295 and 0.60 min -1 at 280) requiring 500 sec to attain 5 half lives. This result contrasts with iron release from the monoferric N-lobe (Fe N hTF) that yielded three rate constants of 20.8, 4.1 and 1.1 min -1 under identical conditions and was complete in 200 sec (25). The slower rate constant for iron release from the C-lobe of Fe C hTF relative to the N-lobe in the Fe N hTF construct is attributed to differences in the second shell residues and in the hinge regions between the subdomains of each lobe.…”
Section: Discussionmentioning
confidence: 74%
“…Both lobes of ICA and the C-lobe of the M subfamily have lost iron-binding capacity (Baker et al 1992; Wang et al 2007). The presence of numerous conserved clade-specific residues in the C-lobes of both of these subfamilies suggests that they have adapted to novel functions.…”
Section: Discussionmentioning
confidence: 99%
“…The following members of this family are recognized in humans: (1) serotransferrin (or serum transferrin), which is expressed in the liver and secreted into the blood serum, but also has a wider tissue expression and a variety of potential functions (Gkouvatsos et al 2012); (2) lactoferrin (Figure 1), named for its expression in milk but expressed in most biological fluids (Levay and Viljoen 1995; GarcĂ­a-Montoya et al 2012); and (3) melanotransferrin, identified as a tumor antigen in melanoma but having a wide but much lower level of expression in normal tissues as well (Rahmanto et al 2012). Well-studied transferrin family members from non-human vertebrates include ovotransferrin, first identified from avian egg white but known to have a wider expression pattern in the domestic chicken (Giansanti et al 2012); and the inhibitor of carbonic anhydrase (ICA) reported from various non-human mammals (Wang et al 2007; Eckenroth et al 2010). …”
mentioning
confidence: 99%
“…As previously described, it contains the signal peptide from hTF, four amino acids from the amino terminus of hTF, a hexahistidine tag, and a Factor Xa cleavage site (19). A single mICA mutant with the S188Y mutation was first produced.…”
Section: Methodsmentioning
confidence: 99%
“…Monoferric N-His-tagged hTF constructs that bind iron only in the N-lobe (N-His Y426F/Y517F hTF-NonGly, designated Fe N hTF) or in the C-lobe (N-His Y95F/Y188F hTF NonGly, designated Fe C hTF) were similarly produced and purified. Fe N hTF served as a control for the W124R/S188Y mutant mICA construct since it binds iron only in the N-lobe (19). The homogeneity of the samples was assessed by SDS-polyacrylamide gel electrophoresis on 10% gels under reducing conditions and was visualized with Coomassie blue dye.…”
Section: Methodsmentioning
confidence: 99%